A case study on the implementation of differentiated instruction in ELT classroom - Erlia Rahman, Sabrina; Fakhruddin, Afief; Syarifah, Eva Fitriani (Concept : Community Concern for English Pedagogy and Teaching, 2024)
This study focused on how English teachers implement differentiated instruction (DI) in English language teaching (ELT) classrooms and the challenges they faced. Differentiated Instruction is a relevant approach because it enables educators to adapt learning content, processes, and products to students' readiness, interests, and learning profiles. This research used a qualitative method with a case study design. The participants were an English teacher and tenth-grade students at a public senior high school in Majalengka. Data were collected through classroom observations and interviews. The findings showed that the teacher used diagnostic assessments to categorize students as auditory, visual, or kinesthetic learners. Learning materials and activities were then adapted accordingly. However, the study also identified challenges, including limited resources, a lack of training, and difficulties managing student groups. The discussion highlights how, with proper support, DI can enhance student engagement and comprehension. In conclusion, DI is an effective and inclusive ELT strategy, but its success depends on continuous teacher development and institutional support. Keywords: Differentiated instruction; English Language Teaching; case study.